Evaluation of inflow/infiltration and flow characteristics for design of sanitary sewers in Skudai, Johor Bahru - Kamran, Kamran (2005)
The design of the sanitary sewer or a treatment plant needs the assessment of the extent of extraneous water that seeps into the system. The study provides the appropriateness of some of the design parameters used by the local engineers. Particular attention is also given to the variation of inflow / infiltration with respect to rainfall occurrence which is found to be very large. The data used in making the evaluation is obtained using the flow-meters for directly measuring the flow in a running sewer line in two different residential areas in ten phases which include both weekdays and weekends, collecting and measuring the amount of water trapped in an abandoned sewer line (field model) continuously for nearly eight months which include both dry and wet periods and also by performing infiltration tests on a laboratory model under saturated and unsaturated conditions to obtain the results in controlled environment. The rainfall is measured using automatic rain-gauge. The results show that the infiltration into the sewers much higher than allowable under Malaysian Standards and infiltration as high as 275.46 liters/day/km-length/mmdiameter is found during wet period. Laboratory tests show results within allowable limits. Based on site study, the design parameters of per capita flow contribution and peak flow factor are found lower than the Malaysian Standard. The results thus obtained are going to be helpful for the municipal agencies and their consulting engineers quantify and simulate rainfall derived infiltration and inflow that affects the sewer systems they design, operate and manage.